Analysis of Teacher Skills in Developing Effective Learning Plans in the Digital Era - Afitzka Al Zahwa; Mawaddah Rahmah; Suci Amaliah Haza; Hadriadi Iskandar Sipayung; Sri Aswinda Harefa (Sean Institute, 2024)
The advancement of digital technology has significantly transformed education , particularly in learning processes increasingly integrated with technology . This study aims to analyze the skills of teachers at MAN 2 Medan in designing effective lesson plans in the digital era. Using a qualitative approach , the research explore the extent to which teachers address challenges such as limited facilities , lack of training , and the gap between technology and its classroom implementation . Findings reveal that while efforts to adopt technology exist , many teachers still struggle to create technology based learning plans relevant to 21st-century students needs . The study concludes that continuous training and improved facilities are strategic steps to enhance teacher competencies , ensuring optimal implementation of technology based learning in the digital era.